Comparison of education using the flipped class, gamification and gamification in the flipped learning environment on the performance of nursing students in a client health assessment: a randomized clinical trial - Raziyeh Ghafouri; Vahid Zamanzadeh; Malihe Nasiri (BMC Medical Education, 2024)
Abstract Background Since effective education is one of the main concerns of every society and, in nursing, can lead to the education of successful people, the development of learning and teaching methods with greater effectiveness is one of the educational priorities in every country. The present study aimed to compare the effect of education using the flipped class, gamification and gamification in the flipped learning environment on the performance of nursing students in a client health assessment. Methods The present study was a Parallel randomized clinical trial study. The participants were 166 nursing students. The clinical trial data was collected from December 14, 2023, to February 20, 2024. The inclusion criteria were nursing students who had passed the first semester, who were willing to participate and install the app on their mobile devices, and who had no experience with the designed application for this study. The participants were allocated to four groups with colored carts. In the first group, teaching was performed via gamification in a flipped learning environment; in the second group, teaching was performed via the gamification method. A flipped class was implemented in the third group. In the fourth group, the usual lecture method was used. The practical performance to assess the physical health assessment with 10 questions using the key-feature questions, along with the satisfaction and self-efficacy of the students, was also checked with questionnaires. Results In this study, 166 nursing students, (99 female and 67 male), with an average (standard deviation) age of 21.29 (1.45) years, participated. There was no statistically significant difference in the demographic characteristics of the participants in the four intervention groups (P > 0.05). Comparing the results before and after the intervention, the results of the paired t test indicated a significant difference in the satisfaction, learning and self-efficacy of the learners (P < 0.001). In the comparison of the four groups, the ANOVA results for the comparison of the average scores of knowledge evaluation and satisfaction after intervention among the four groups indicated a statistically significant difference (P < 0.001). When the knowledge evaluation scores of the groups were compared, the scores for gamification in the flipped learning environment were significantly different from the other methods (P < 0.05), and there was no significant difference between the scores for the flipped class and lecture methods (P = 0.43). According to the ANOVA results, when comparing the satisfaction scores of the groups, the students in the flipped learning environment and gamification groups were more satisfied than the flipped class and lecture groups (P < 0.01). Conclusion Based on the results of the present research, it can be concluded that teaching methods have an effect on students’ learning and satisfaction. The teaching method has an effect on the satisfaction of the students, and the use of the flipped class method with the use of gamification was associated with more attractiveness and satisfaction in addition to learning. Teachers can improve the effectiveness of education with their creativity, depending on situation, time, cost, and available resources, by using and integrating educational methods.